Biomechanical basis of human movement - Hamill, Joseph PhD; Knutzen, Kathleen M. PhD; Derrick, Timothy R. PhD (Wolters Kluwer, 2022)
Master the full continuum of human movement potential with this rigorous yet approachable introduction to biomechanics. Focusing on the quantitative nature of biomechanics, Biomechanical Basis of Movement, fifth edition applies laws of motion and mechanics to in-depth analysis of specific movements, integrating current literature, meaningful numerical examples, relevant applications, hands-on exercises, and functional anatomy, physics, calculus, and physiology for a confident, comprehensive understanding of human movement.
1. Basic terminology -- 2. Skeletal considerations for movement -- 3. Muscular considerations for movement -- 4. Neurological considerations for movement -- 5. Functional anatomy of the upper extremity -- 6. Functional anatomy of the lower extremity -- 7. Functional anatomy of the trunk -- 8. Clinical considerations: tissue deterioration or injury -- 9. Linear kinematics -- 10. Angular kinematics -- 11. Linear kinematics -- 12. Angular kinematics -- 13. Types of mechanical analyses
Includes accompanying online ancillary resources
Keywords: Human mechanics